DINAMIKA PEMIKIRAN FIKIH MAZHAB INDONESIA (Perspektif Sejarah Sosial) - Mukri, Moh (Analisis: Jurnal Studi Keislaman, 2011)
Sociologically  and culturally  speaking,  Islamic  law is the law that flows and deeply stem from cultural roots of community.  It presents together with the presence of Islam. In the current days of Indonesia, however, Islamic law is in part an unwritten  law, in addition to the trade mark that is still characteristically  attached to the Middle East. These are the reasons why a number of Indonesian Muslim scholars then gave rise to the indigenization  of Islamic law with a variety of ideas and namings. This paper attempts to depict the journey of the indigenization  of fiqh (Islamic law) discource  in Indonesia  by using analysis of social history. There were some important figures offered constructive  and  paradigmatic  jurisprudence  format  of  Indonesian fiqh. Such important  figures that will be analysed  in this paper are Hasbi ash-Shiddiqy as the originator of the early Indonesian fiqh, and Hazairin who initiated the Indonesian madzhab or Indonesian Shafi’i plus school projected to include the national inheritance law. Then KH Sahal Mahfuz, the originator of an Indonesian social jurisprudence, and the last Gus Dur (Abdurrahman Wahid KH), who offered the genuine ideas of the indigenization  of Islam and contextualization  of Islamic jurisprudence.